Significant deposits of minerals in the table D. I. Mendeleev: national dimension - Бейдик, О. (Київський національний університет імені Тараса Шевченка, 2018)
The distribution of chemical elements and deposits of minerals is heterogeneous on the Earth. This heterogeneity reflects the following chain of levels of mineral resource supply of countries and territories: very low → low → average → high → very high. Extreme links of this chain can be represented, for example, in the Republic of Korea (a very low level of mineral supply) and the South African Republic (very high level of mineral supply). Ukraine, according to various estimates, occupies the second (low) or third (middle) level in this rank. This publication serves as an objective basis for such assessments and aims as to demonstrate a certain raw material and energy independence of the quarry with respect to the provision of the most important minerals (this is demonstrated by the “mineral-raw” filling of the table by D. I. Mendeleev). The systemic representation of Ukraine’s provision of mineral resources in general and regions (Donbas, Crimea, etc.) or economic regions (in some cases, in oblasts) provides a table «Deposits of minerals in Ukraine in the context of economic regions in the periodic system of chemical elements (tables by D. I. Mendeleev)». The high level of provision of Ukraine’s territory with mineral resources in the context of economic-geographical regions has been confirmed. The periodic system of chemical elements (table by D. I. Mendeleev) is strengthened by data on the distribution of mineral raw materials and minerals in the context of economic-geographical regions of Ukraine. The highlighted problem has confirmed the high density of interdisciplinary connections (geography, geology, geochemistry, economics, regionalistics, zoning). The presented material reveals a decent level for developing strategies for socio-economic development of the regions, the given data can be implemented in the latest programs of reformed education of Ukraine.

Підтверджено високий рівень забезпечення території України мінерально-сировинними ресурсами в розрізі економіко-географічних районів. Періодична система хімічних елементів (таблиця Д. І. Менделєєва) посилена даними щодо розподілу мінерально-сировинних ресурсів та корисних копалин в розрізі економіко-географічних районів України. Висвітлена проблематика підтвердила високу щільність міжпредметних зв’язків (географія, геологія, хімія, геохімія, економіка, регіоналістика, районування). Викладений матеріал може виступати певним важелем розробки стратегій суспільно-економічного розвитку регіонів, наведені дані можуть бути впроваджені в новітні програми реформованої освіти України.
Основні родовища корисних копалин у таблиці Д. І. Менделєєва: національний вимір
Алампиев П. М. Экономическое районирование СССР : в 2-х кн. / П. М. Алампиев. – М., 1959-1963. – Кн. 1. – М. : Госпланиздат, 1963. – 263 с. ; Кн. 2. – М. : Экономиздат, 1963. – 247 с. Бейдик О. О. Географія : Посібник для вступників до вищих навчальних закладів – 2-е вид. / О. О. Бейдик, М. М. Падун. – К. : Либідь, 1996. – 304 с. Геология СССР : в 48-и т. / гл. ред. П.Я. Антропов. – Т. V: Украинская СССР и Молдавская СССР. Ч. 1. Геологическое описание платформенной части. – М. : Госнаучтехиздат литературы по геологи и охране недр, 1958. – 1000 с. Металічні і неметалічні та корисні копалини України / Гурський Д. С., Єсипчук К.Ю., Калінін В.І. та ін. : у 2-х кн. – К. – Львів : Центр Європи, 2006. – Т. І : Металічні корисні копалини. – 785 с. ; Т. ІІ : Неметалічні корисні копалини. – 552 с. Паламарчук М. М. Економічна географія Української РСР (з основами теорії). – К. : Рад. школа, 1975. – 312 с. Поповкін В. А. Регіонально–цілісний підхід в економіці / В. А. Поповкін ; НАН України, Рада по вивченню продуктивних сил України. – К. : Наукова думка, 1993 . – 219 с. Пістун М. Д. Основи теорії суспільної географії / М.Д. Пістун. – К.: Вища школа, 1996. – 231 с. Свідоцтво про реєстрацію авторського права на твір №75014. Україна. Видатні родовища корисних копалин в таблиці Менделеєва: світовий та національний вимір / Бейдик О. О. – 27.11.2016. Соціально–економічна географія України : Навч. посіб. / За ред. О.І. Шаблія. – Львів : Світ, 2000. – 679 с. Соціально-економічне районування України / Долішній М. І., Паламарчук М. М., Паламарчук О. М., Шевчук Л. Т. ; НАН України. Інститут регіональних досліджень. – Львів, 1997. – 50 с.
Keywords: мінерально-ресурсна база України; корисні копалини; родовища; система хімічних елементів; таблиця Д.І. Менделєєва; mineral resource base of Ukraine; minerals; deposits; the system of chemical elements; D. I. Mendeleev table